Far Off Equilibrium Dynamics in Clusters and Molecules - Mai Dinh, Phuong; Vincendon, Marc; Heraud, Jordan; Suraud, Eric; Reinhard, Paul-Gerhard (Frontiers in Physics, 2020)
This brief review illustrates on a few typical applications fully fledged dynamical simulations of finite electronic systems (atoms, molecules, clusters) using time-dependent density-functional theory (TDDFT). It concentrates on aspects which are different from nuclear applications. These are: the correct handling of electron emission, the self-interaction correction, the enormous versatility of laser excitation to probe systems properties, and with it the exploitation of detailed observables of electron emission as photo-electron angular distributions and photo-electron spectra (PES). Finally, we demonstrate the impact of electronic dissipation putting question marks on the reliability of TDDFT simulations over long times.